2016
DOI: 10.1080/02699931.2016.1152232
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive trait anxiety, stress and effort interact to predict inhibitory control

Abstract: Few studies have focussed on the link between anxiety and inhibitory control in the absence of stimulus-driven external threat. This two-part experiment examined the interactions between (1) somatic trait anxiety, somatic situational stress (i.e. threat of electric shock), and effort, and (2) cognitive trait anxiety, cognitive situational stress (i.e. ego-threat instructions), and effort, on inhibitory processes using a Go-No-Go paradigm. Trait anxiety was operationalised using questionnaire scores and effort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
2
33
1
Order By: Relevance
“…Similarly, Edwards et al (2015Edwards et al ( , 2017 investigated potential impacts of anxiety on executive functions. They manipulated stress by informing participants that the upcoming tasks were indicative of intelligence, and that they were performing worse than expected.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Edwards et al (2015Edwards et al ( , 2017 investigated potential impacts of anxiety on executive functions. They manipulated stress by informing participants that the upcoming tasks were indicative of intelligence, and that they were performing worse than expected.…”
Section: Studymentioning
confidence: 99%
“…Again, to test our prediction that trait cognitive anxiety is the specific component that will impact task performance, it was necessary also to test the effects of the somatic component (e.g. Edwards et al, 2017).…”
Section: Studymentioning
confidence: 99%
“…It was found that heightened anxiety vulnerability was associated with elevated attentional distraction by the distractor stimuli. Similarly, Edwards et al showed that heightened anxiety vulnerability was associated with reduced inhibitory control during a No-Go paradigm, which requires participants to execute volitional responses on target-absent trials and inhibit responding on relatively rare and randomly presented target-present trials [ 11 ]. Given these and other findings demonstrating association between elevated anxiety vulnerability and reduced inhibitory attentional control performance (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the scores on STAI-S were somewhat low irrespective of the level of trait anxiety, it is possible that intense state anxiety might affect executive processes under stressful situations. This possibility is becoming further elucidated in recent studies [33] [34].…”
Section: Discussionmentioning
confidence: 99%